Historical Aspect of the Formation of the System of Art Educational Institutions in Ukraine - Bokshan, Anna (Pedagogical Discourse, 2025)
It is proved that the formation of the system of art educational institutions laid the foundation for the development of professional art education in Ukraine. The development of culture, customs and aesthetic ideas of people, as well as the need to train qualified art professionals, became the basis for the creation of specialised educational institutions in different regions of Ukraine. The second half of the nineteenth century was marked by the opening of: painting schools (Kyiv Public School of Painting of M. Buialovskyi, Odesa Drawing School, Kharkiv School of Drawing of M. Raievska-Ivanova, Myrhorod Art and Industrial School named after Mykola Hohol, Kamianets-Podilskyi Art and Industrial School, etc.); art and industrial schools and colleges (Lviv Industrial Schools, Kosiv Industrial School, etc.). It is determined that under the influence of ideological views of social transformation, artistic and industrial education gained priority in artistic educational institutions of Ukraine. The author analyses the formation of modern educational complexes «college - institute – academy» and their positive dynamics (Lviv National Academy of Arts, Transcarpathian Academy of Arts). It is considered that it was in the 20s of the XX century that design education began to emerge in Ukraine, which became a natural continuation and development of artistic and industrial education. This period was an important stage in the formation of new directions in art education, which took into account the processes of industrialisation and modernisation of the society and the introduction of the speciality «Design» (Academy of Fine Arts and Architecture, National Forestry University of Ukraine, Kharkiv State Academy of Design and Art, etc.). It is determined that the analysis of the activities of higher art and artistic and industrial educational institutions gives grounds to assert that they have provided and continue to provide a high level of professional training of graduates in the field of art.